ANALISIS FUNGSI BADAN PERMUSYAWARATAN DESA DALAM PENYELENGGARAAN PEMERINTAH DESA DI DESA BALASARI KECAMATAN POLEANG BARAT KABUPATEN BOMBANA - Anis Ribcalia Septiana; Achmad Lamo Said; Anis Ribcalia Septiana (Journal Publicuho, 2024)
The purpose of this study was to determine the function of the Village Consultative Body (BPD) in Balasari Village, Bombana Regency. The research method used is Qualitative Descriptive. The results of this study indicate that the function of the BPD based on Permendagri Number 110 of 2016 articles 31 to 51 and article 71 has not been running optimally because the first function has been implemented properly as seen in Village Regulation Number 2 of 2023 concerning Direct Cash Assistance for Village Funds for the 2023 Budget Year, but its transparency is minimal, not everyone knows about the existence of the Village Regulation in Balasari Village. The second function of the BPD is not maximally responsible because most of the aspirations that have been collected have not been channelled. The third function of the BPD is not implemented in accordance with compliance with legal regulations, this is because supervision of the village head's performance is only carried out during his free time.